2021
DOI: 10.2147/pgpm.s324410
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Very Important Pharmacogenomics Variants in the Chinese Lahu Population

Abstract: Background Genetic polymorphism, obviously, has a potential clinical role in determining differences in drug efficacy; however, there are no reports about the pharmacogenomic information of the Lahu population. Therefore, our research aimed to screen the genotypic frequencies of the very important pharmacogenomics (VIP) mutations and determined the differences between Lahu and the other 11 populations. Methods Agena MassARRAY (AgenaMassARRAY) single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The genetic background plays a crucial role in pharmacological reactions 6 11 . Over the last decades, pharmacogenetic studies identified several pharmacogenes and functional variants associated with drug response and helped in the identification of genes that can explain variation in drug response, known as pharmacogenes, as well as pharmacodynamics 10 15 . Variant–drug response associations have been established for many of these genes and this information can be translated into the clinical setting 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The genetic background plays a crucial role in pharmacological reactions 6 11 . Over the last decades, pharmacogenetic studies identified several pharmacogenes and functional variants associated with drug response and helped in the identification of genes that can explain variation in drug response, known as pharmacogenes, as well as pharmacodynamics 10 15 . Variant–drug response associations have been established for many of these genes and this information can be translated into the clinical setting 16 18 .…”
Section: Introductionmentioning
confidence: 99%